Peran Guru Dalam Menanamkan Nilai-Nilai Pancasila Pada Peserta Didik Di SD Negeri 62 Banda Aceh - Syarful Rahmawati; Sulaiman Sulaiman; Soedirman Soedirman (Elementary Education Research, 2023)
This study aims to describe the teacher's role in instilling Pancasila values in students. The approach in research is qualitative and descriptive research type. The subjects in the study were 6 class teachers at SDN 62 Banda Aceh. Data collection techniques through observation and interviews. Data analysis techniques in this study used data reduction, data presentation and conclusion. Based on the research results, it is known that teachers in grades I-VI have played the role of educators, mentors, coaches in instilling Pancasila values, namely the value of divinity and the value of unity, teachers in grades I-III have not implemented human, populist, and justice values, while teachers in grades IV-VI has played a role in instilling the values of humanity, democracy, and justice. The conclusion in this study is that teachers have played a role in instilling Pancasila values, namely class IV to class V but there are also obstacles in instilling Pancasila values in students, unlike the case with class I, II, III teachers, they still have not fully played a role as educators, trainers and mentors because some of the Pancasila values have not been implemented.